Vitamin E dan Malondialdehid Darah Wanita Hamil di Daerah Endemik Gondok di Jawa Tengah - Prasetyastuti Sunarti (Berita Kedokteran Masyarakat (BKM), 2008)
Background: Usually, people who live in goiter areas have iodine deficiency. Iodine deficiency increases thyroid stimulating hormone (TSH) in blood that can promote product of hydrogen peroxide. Hydrogen peroxide can produce free radicals that can promote lipid peroxidation. One of the lipid peroxidation products is MDA (malondialdehyde). Vitamin E is an antioxidant that can trap free radical in cell membrane and plasma lipoprotein so it can protects lipid peroxidation by free radical.Objectives: The aim of this study was to find out whether there is some possibility of differences between vitamin E and MDA concentrations in the blood of pregnant women living in goiter and those of women non goiter areas.Method: A Cross Sectional study was conducted, in which 60 women from goiter endemic and 60 women from non goiter endemic were randomly selected to serve as subjects. The blood sample was taken from venous cubiti. Vitamin E was measured by spectrofluorometer and MDA was measured by spectrophotometer. T test was employed to analyze the data.Results: The vitamin E level of the women living in goiter and non goiter endemic areas, 33.17 +  9.13 ìg/ml versus 32.39 + 11.13 ìg/ml respectively, were not significantly different (p=0.677; CI:-4.455; 2.905), but the MDA level of those, 12.07 + 2.75 nmol/ml versus  8.73 + 3.04 nmol./ml respectively, were significantly different (p=0.000; CI:- 4.386; -2.287). The correlation between vitamin E and MDA levels was not significant (p=0.403; CI:-0.034; 0.085).Conclusion: There is significantly difference of MDA level of the women living in goiter and non goiter endemic areas but the MDA was not correlated with the vitamin E level.Keywords : vitamin E, malondialdehyde, pregnant, goiter